Impatiens yixiangensis (Balsaminaceae), a new species from Sichuan, China - Huang, Han-Wen; Wang, Zi-Yi; Li, Rong (Phytotaxa, 2025)
Impatiens yixiangensis, a new species of Balsaminaceae from southwest China, is described and illustrated. It closely resembles I. imbecilla, I. faberi, I. wawuensis and I. baishaensis, but is distinguishable by its solitary flowers, the inner surface of the united lateral petals being densely puberulent at the central part, a short rectangular auricle, and the slightly incurved spur. Phylogenetic analysis based on three genetic regions further supports the separation of I. yixiangensis from these morphologically similar species.